PERSEPSI WISATAWAN PERANCIS TERHADAP “THE ISLAND OF PARADISE” - Resmayasari, Ira (Jurnal Ilmiah Pariwisata, 2012)
The purpose of this research is to determine the perception or opinion of French tourist about Bali, whether on its nature, environment, community, or about tourism in Bali. In addition, this research aims to verify the assumption that Bali is truly “The Island of Paradise”. In fact, based on the result of the survey, French tourists have a good perception on Bali. They perceived Bali as a place that has so many natural beauties, a unique island, and different from any other place so that tourists can feel the comfortable, safe, peaceful and tranquil atmosphere. They were also impressed with the hospitality of local communities.The research is obtained through the procedures of data collection through observation, interviews, and documents from the empirical world. The method used in this research is a design of a survey that was conducted through a questionnaire distributed to French tourists who have visited Bali. The result of the survey is then included in the statistics analysis, which is described descriptively.This research was also conducted through the literature of tourism studies as a supporting research. Data collection is done by collecting and analyzing the data through the literature relating to issues to be investigated; such as the textbooks, scientific journals, and other sources, such as the utilization of Internet.